Technical and tactical game analysis of elite basketball in three different levels - Lehto, H.; Häyrinen, M.; Fay, T.; Tammivaara, A.; Dettmann, H. (2010)
From all offenses, fast break and transition offenses were the most successful ones and thus the opportunity to these types of offenses should be used in order to improve the successfulness of the offense. Furthermore, direct put backs from offensive rebounds should be used as they are an effective way to score. In addition, more specific training could be directed to improving the special standing still situations in the offensive end (sideline and baseline out of bounds) as at all levels the number and effectiveness of direct attempts from these set plays was rather low. The most dominant type of defense in the analyzed matches was the active man-to-man defense and the zone defense was used only in 8 % of the time. The shots from closer distance (paint shots) were the most effective ones. There wasn`t a big difference in the success of shots between the 2 point area outside the paint and 3 point areas but clearly more points would be scored from 100 shots from 3 point area when compared to 2 point area. Thus it could be recommended that shot is taken behind the 3 point line if the shot from the paint isn`t possible. It was also clearly presented that the good shots succeed a lot better when compared to the bad shots. Based on these results, it could be strongly recommended that the bad shots are not taken unless no other option is available. Except for Team Finland, the use of pick`n`rolls did not improve the success of the offense. However, it was found that when the pick`n`roll was used during the offense, more offenses led to a shot and less turnovers occurred and thus the use of pick`n`rolls could be beneficial. Furthermore, when pick`n`roll was used, the shot tended to come from longer range and 3 point shots succeeded better. There was a clear tendency in the increasing use of the pick`n`rolls according to the higher level and in the Olympic matches pick`n`rolls were used in 49 % of the ½-court offenses. The offenses using 3-5 passes were the most common ones. It seems not to be beneficial to use more than 5 passes during the offenses as in the ½-court offenses the increasing number of passes did not affect on the successfulness of the offense. Based on the analyzed matches the tempo of the game was the highest in the Olympic level where the number of all offenses and possessions was higher than in the national team or Finnish league matches. The number of offenses and possessions was the lowest in the national team matches, mainly due to the style of play by the opponents of Team Finland as many of them were teams who tend to control the ball more.